Thin films of electron donor–acceptor complexes: characterisation of mixed-crystalline phases and implications for electrical doping. Issue 2 (1st December 2021) - Opitz, Andreas; Duva, Giuliano; Gebhardt, Marius; Kim, Hongwon; Meister, Eduard; Meisel, Tino; Beyer, Paul; Belova, Valentina; Kasper, Christian; Pflaum, Jens; Pithan, Linus; Hinderhofer, Alexander; et al.
Abstract : For electron donor–acceptor complexes a link will be established between optical, structural and vibrational properties of EDA complexes as well as the electrical doping by them. Abstract : Electron donor–acceptor (EDA) complexes are of interest as low-band gap molecular semiconductors and as dopants for molecular semiconducting matrices. This contribution establishes a link between optical, structural and vibrational properties of EDA complexes as well as the electrical doping by them. We comprehensively characterise co-deposited films of the donors dibenzotetrathiafulvalene and diindenoperylene and the acceptors tetracyanonaphthoquinodimethane and its hexa-fluorinated derivative. All co-deposited donor:acceptor systems form mixed crystalline structures and the EDA complex is characterised by the complex-related absorption and X-ray scattering features. The absorption energies of the analysed EDA complexes cross the neutral-to-ionic boundary. The degree of charge transfer is determined by vibrational spectroscopy. Here, strong spatial anisotropy is found for the diindenoperylene containing complexes. The electrical transport measurements reveal an exponential relation between electrical conductivity and activation energy of transport for all complex-doped systems. We show with this result that doping via complexes has the same dominant activation process as doping via integer charge transfer, which is the separation of Coulombically bound charges. Our results are put in a broader context and we provide an outlook on future possibilities and research on EDA complexes.